2012
DOI: 10.1603/en12222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flour Conditioning on Cannibalism of <I>T. castaneum</I> Eggs and Pupae

Abstract: Cannibalism is a very important factor regulating population dynamics of the red flour beetle. After several days of feeding, the flour becomes conditioned by the beetles, which can affect rates of cannibalism. Flour conditioning is caused by an accumulation of feces, pheromones, and ethylquinone, which is a repellent produced by the beetles. We determined the effect of five different levels of flour conditioning on cannibalism of red flour beetle eggs and pupae by adult and larval stages. Larvae had the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
(7 reference statements)
1
9
0
Order By: Relevance
“…This finding has been reported by many other authors as well (Alabi et al, 2008;Flinn & Campbell, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…This finding has been reported by many other authors as well (Alabi et al, 2008;Flinn & Campbell, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, we find that in the absence of an intact flour microbiome, adult beetles and larvae increase egg cannibalism. Since flour beetle cannibalism typically increases in poor resources [28,30,31], we suggest that the flour microbiome may either directly or indirectly signal resource quality.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, we find that in the absence of an intact flour microbiome, adult beetles and larvae increase egg cannibalism. Since flour beetle cannibalism typically increases in poor resources [ 28 , 30 , 31 ], we suggest that the flour microbiome may either directly or indirectly signal resource quality. Pathogen resistance was the only tested fitness metric where we did not find an impact of the microbiome; although prior work suggests that the beetle microbiome is critical for the formation of immune memory against the same species of pathogen used in our assays [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important characteristic of our proposed models is the consideration of the cannibalism effect on the prey, since several studies have reported the stabilizing consequences of cannibalism in predator-prey systems [12,13]. There are numerous examples in nature where cannibalism is present, for example, the confused flour beetle (Tribolium confusum) [14], the red flour beetle (Tribolium castaneum) [15], and the Dungeness crab (Metacarcinus magister) [16].…”
Section: Introductionmentioning
confidence: 99%